Internal fouling during microfiltration with foulants of different surface charges - Trinh, Thien An (2022)
In view of the inevitability of membrane fouling, it is critically important to understand the underlying mechanisms to alleviate fouling and thereby improve the feasibility of membrane-filtration for more applications. This study was targeted at understanding the internal membrane fouling mechanisms by three types of polystyrene (PS) particles (sized at ~ 0.45 μm; different surface charges) during microfiltration with the same polycarbonate track-etched (PCTE) membrane (nominal pore size of 2 μm). Optical coherence tomography (OCT) technique, which was employed to monitor membrane fouling, indicated greater extents of particle deposition in the case of the positive and less negative PS particles, which is consistent with the more severe flux declines relative to the more negative PS particles. The new fouling model developed that additionally accounts for internal cake filtration, on top of the well-reported pore constriction and pore blockage, revealed the fouling mechanisms at play. For the positive PS particles, the attractive particle-membrane interaction led to a more homogeneous layer-by-layer cake growth, which resulted in denser packing in the pore and higher internal cake resistance, and thereby the worst flux decline. In contrast, for the negative PS particles, the repulsive particle-particle and particle-membrane interactions resulted in more random deposition of the particles inside the pores, resulting in more extensive pore constriction and blockage, as well as lower resistance of the internal cake. This study underscored the importance of surface charge in internal fouling and provided insights on the lesser reported internal fouling mechanisms.